Efek pemberian madu terhadap lesi hepar maternal mencit (mus musculus) dan gangguan perkembangan fetus yang dipapari monosodium glutamate (MSG) selama masa kehamilan - Sufitni dr; Delyuzar dr; Emita Sabri (Fakultas Kedokteran USU, 2013)
Introduction : Monosodium glutamate (MSG), a food additive that is still a controversial, where some states are safe, but partly it's harmful to health. High consumption of MSG will increase glutamate metabolism. It will increase free radical, which harmful to body. Honey as antioxidant can remove free radical. Giving honey in pregnant mice after giving MSG, will reduce the negative impact of MSG.The purpose of study was to determine the effects of honey therapy against fetal development disorder of mice and hepatic lesions induced by giving of MSG during pregnancyMethods : The study is purely experimental with a completely randomized design (CRD), which consists of five groups, there are one control group and four treatment groups. The control group was given distilled water only during gestation days 0-18. The first treatment were given MSG 4mg/g body weight/day, the second treatment were given honey 0.15g/20g body weight /day, and the fourth treatment were given MSG 0.15 g/20g body weight/day and honey 4mg/g body weight/day, as long as 0- 18 days of gestation. The third treatment groups were given MSG 4mg/g body weight/day on days 0-7 of pregnancy, and continued provision of honey 0.15g/20g body weight/day on days 8-18 of pregnancy. At gestational age 18 days, each treatment and control mice were killed by cervical dislocation and then dissected for liver and fetuses removalResult : Giving of high doses of MSG to mice during pregnancy, give embriotoxic effect, characterized by decreased the number of live fetuses up to 54.9% (P = 0.003) and increased the number of embrio resorption up to 58.86% (P = 0.02), and hepatotoxic effect compare control with P value = 0.041. Giving honey can reduce hepatotoxic and embriotoxic of MSG effect, particularly they are giving together will increase the number of live fetuses up to 100% and decrease the number of embrio resorption up to 0%.Key words : monosodium glutamate (MSG); fetal; development disorder; mice; pregnancy; hepatic lesion77 |